2014
DOI: 10.1128/jb.02095-14
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division Resets Polarity and Motility for the Bacterium Myxococcus xanthus

Abstract: e Links between cell division and other cellular processes are poorly understood. It is difficult to simultaneously examine division and function in most cell types. Most of the research probing aspects of cell division has experimented with stationary or immobilized cells or distinctly asymmetrical cells. Here we took an alternative approach by examining cell division events within motile groups of cells growing on solid medium by time-lapse microscopy. A total of 558 cell divisions were identified among appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, whether RomR Bd as a growth-controller is a scaffold protein that recruits other proteins to the poles, or has a direct role in growth, is currently unknown. Harvey and coworkers 33 established that RomR Mx is recruited to the site of M. xanthus cell division to reset polarity for the daughter cells. This allows asymmetric localisation, important for motility in the parent cell, to be emulated in the daughter cells 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether RomR Bd as a growth-controller is a scaffold protein that recruits other proteins to the poles, or has a direct role in growth, is currently unknown. Harvey and coworkers 33 established that RomR Mx is recruited to the site of M. xanthus cell division to reset polarity for the daughter cells. This allows asymmetric localisation, important for motility in the parent cell, to be emulated in the daughter cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Harvey and coworkers 33 established that RomR Mx is recruited to the site of M. xanthus cell division to reset polarity for the daughter cells. This allows asymmetric localisation, important for motility in the parent cell, to be emulated in the daughter cells 33 . They suggested that RomR Mx may interact with proteins of the developing cell poles; it is therefore conceivable that RomR Bd works together with polar growth components in B. bacteriovorus , having evolved a key role in establishing polarity during cell division 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This sample and imaging method was chosen to produce experimental results with low average contrast (0.52), far outside of the training distribution. Sample preparation and microscope configuration is described in [45, 46]: unlabeled bacteria are illuminated with 458 nm laser to excite flavins in the bacteria, resulting in autofluorescence. The microscope is configured as an widefield epi-fluorescence microscopy using a single dichroic mirror as both excitation and emission filter, resulting in the excitation light leakage and/or back scattering being detected by the imaging EM-CCD.…”
Section: Model Validationmentioning
confidence: 99%
“…Simultaneous examination of bacterial division and motility is extremely challenging; thus the relationship between cell division and cell motility is poorly understood. A recent study showed that Myxococcus xanthus stops its motility during its division and resumes only after completion of the division ( 38 ). Similarly, during the exponential growth of E. coli , the flagellar gene expression is repressed and bacterial adhesion is enhanced ( 39 ).…”
Section: Discussionmentioning
confidence: 99%